Arguments, stories and criminal evidence: a formal hybrid theory - Bex, Floris J. (Law and philosophy library, 2011)
Reasoning with criminal evidence -- Two approaches to reasoning with evidence : arguments and stories -- A hybrid theory of stories and arguments -- A formal logical hybrid theory of argumentation and explanation -- Case study : Murder in Anjum -- Related research on reasoning with criminal evidence